Squarate-tethered enantiomeric Imido-Pd(II) cages for recognition and separation of chiral organic molecules - Jose, Cavya; Sarkar, Meghamala; Rajasekar, Prabhakaran; Tewari, Tanuja; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2023)
Chiral coordination cages have emerged as an efficient platform for enantioselective processes via host-guest interactions. Here, we report an enantiomeric pair of tetrahedral cages of formula [(Pd-3[PO(N(*CH(CH3)Ph)(3)])(4)(C4O4)(6)] supported by chiral tris(imido)phosphate trianions and squarate (C4O4)(2-) linkers. These cages exhibit unusual coordination isomerism for Pd(II)-linker bonds compared with the other Pd(II) cages of this family. Further, they were employed for the recognition and separation of small chiral molecules containing various functionalities. High enantioselectivities of 67 and 41 were found in the case of R-4-hydroxydihydrofuran-2(3H)-one and S-epichlorohydrin, recognized by the R-isomer of the cage. Chiral separation studies showed remarkable enantiomeric excess values of 93 and 85% for S-epichlorohydrin and R-4-benzyl-2-oxazolidinone, respectively, from their racemic mixtures. These studies showcase the potential of coordination cages for enantioselective applications.

Portal substituent modulations in chiral imido-Pd(II) cages for the enhanced separation of styrene oxide enantiomers - Jose, Cavya; Sarkar, Abhradeep; Khopade, Kishor V.; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2025)
Sensing and separation of enantiomers are crucial for the synthesis of biologically relevant compounds as well as for applications in catalysis and pharmaceutical development. Chiral coordination cages have gained significant attention as effective platforms for enantioselective processes through their well-defined, tunable cavities that facilitate host-guest interactions. In this study, we systematically explored the enantioselective binding and separation properties of two tetrahedral Pd(II) cages, 1-R and 2-R, with the molecular formula [Pd3(PO[N(RCH(CH3)Ph)3])4(C6O4X2)6] (X = Cl for 1-R, and X = F for 2-R). Their enantioselective abilities were investigated for small chiral molecules with diverse functional groups. Notably, the 2-R cage demonstrated a high enantioselectivity value of 88 for R-styrene oxide. Chiral separation experiments further revealed impressive enantiomeric excess (ee) values of 98% for R-styrene oxide from their racemic mixtures upon desorption from 2-R. The enhanced selectivity and separation efficiency were attributed to an optimal guest-to-cavity fit and the presence of multiple interaction sites within the host framework. Remarkably, portal substituent modulation in 2-R led to a 16-fold enhancement in enantioselective separation efficiency compared to 1-R, primarily due to improved portal dimensions, tighter molecular packing, and increased hydrogen bonding interactions. These findings highlight the potential of neutral chiral coordination cages for various enantioselective applications.